Developing Secondary Mathematics Teacher Leaders: A Multi-Year Curriculum for Inservice Teacher Excellence - Jeremy Zelkowski; Bill Bergeron; Jim Gleason; Martha Makowski; Robert Petrulis (Education Sciences, 2025)
In response to systemic inequities in mathematics education, we developed and evaluated a five-year, multi-phase curriculum model to cultivate effective secondary mathematics teacher leaders. Supported by NSF Noyce Master Teacher Fellowships, the APLUS in MATH (APLUS in Math: Alabama Practitioner Leaders for Underserved Schools in Mathematics) program engaged 22 inservice teachers through graduate coursework, National Board Certification preparation, and leadership project development. Using a mixed-methods design, we analyzed data from classroom observations (MCOP2), National Board Certification assessments, course performance ratings, and teacher leadership project proposals. Results indicate significant improvements in instructional practices, content knowledge, and leadership readiness. Findings underscore the importance for sustained, structured professional development to prepare teachers as instructional experts and change agents in high-need educational contexts.